Pelestarian Nilai-Nilai Leluhur melalui Upacara Pernikahan Adat di Kampung Naga - Ahmad Hamdi; Sri Rahayu Pudjiastuti; R. Mochammad Rachmat; Abdul Hakim; Rahmatullah Sidik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The traditional wedding ceremony in Kampung Naga is not merely a ritual but also the heart of the community’s social life. In the face of social change dynamics, the indigenous people of Kampung Naga have successfully preserved their traditional wedding customs. This study aims to uncover each stage of the ceremony, from preparation to the main event, involving the active participation of all community members, and to analyze how the traditional wedding ceremony in Kampung Naga adapts to modern influences while maintaining core values. Through a qualitative case study approach, this research reveals the strategies used by the community to maintain the relevance of wedding traditions in the context of modern life. The study finds that each stage of the ceremony, from preparation to the main event, is rich with symbols reflecting traditional values such as mutual assistance, simplicity, and respect for ancestors. The concept of “pondok lengkah,” associated with women, also adds a unique dimension to the dynamics of marriage within this community. This research highlights how the wedding ceremony serves not only as a religious ritual but also as a means to strengthen cultural identity and preserve ancestral values.